The emergence of embedded structure: insights from Kafr Qasem Sign Language - Kastner, Itamar; Meir, Irit; Sandler, Wendy; Dachkovsky, Svetlana (Frontiers in Psychology, 2014)
This paper introduces data from Kafr Qasem Sign Language, an as-yet undescribed sign language, and identifies the earliest indications of embedding in this young language. Using semantic and prosodic criteria, we identify predicates that form a constituent with a noun, functionally modifying it. We analyze these structures as instances of embedded predicates, exhibiting what can be regarded as very early stages in the development of subordinate constructions, and argue that these structures may bear directly on questions about the development of embedding and subordination in language in general. Deutscher (2009) argues persuasively that nominalization of a verb is the first step -- and the crucial step -- towards syntactic embedding. It has also been suggested that prosodic marking may precede syntactic marking of embedding (Mithun 2009). However, the relevant data from the stage at which embedding first emerges have not previously been available. Kafr Qasem Sign Language might be the missing piece of the puzzle: a language in which a noun can be modified by an additional predicate, forming a proposition within a proposition, sustained entirely by prosodic means.